Utilization of coupled eigenmodes in Akiyama atomic force microscopy probes for bimodal multifrequency sensing. (5th November 2022) - Kort-Kamp, Wilton J M; Murdick, Ryan A; Htoon, Han; Jones, Andrew C
Abstract: Akiyama atomic force microscopy probes represent a unique means of combining several of the desirable properties of tuning fork and cantilever probe designs. As a hybridized mechanical resonator, the vibrational characteristics of Akiyama probes result from a complex coupling between the intrinsic vibrational eigenmodes of its constituent tuning fork and bridging cantilever components. Through a combination of finite element analysis modeling and experimental measurements of the thermal vibrations of Akiyama probes we identify a complex series of vibrational eigenmodes and measure their frequencies, quality factors, and spring constants. We then demonstrate the viability of Akiyama probes to perform bimodal multi-frequency force sensing by performing a multimodal measurement of a surface's nanoscale photothermal response using photo-induced force microscopy imaging techniques. Further performing a parametric search over alternative Akiyama probe geometries, we propose two modified probe designs to enhance the capability of Akiyama probes to perform sensitive bimodal multifrequency force sensing measurements.